"El siglo de la empresa" - Morales Gutiérrez, Alfonso Carlos (Revista de Fomento Social, 2008)
Reseña de la obra de: SALAS FUMÁS, V. (2007) El siglo de la empresa. Madrid–Bilbao, Fundación BBVA, 207 pp.